Decomposition of and nutrient dynamics in leaf litter and roots of Poa ligularis and Stipa gyneriodes - Moretto, Alicia Susana (2003)
A field experiment was conducted in a temperate semi-arid grassland of central Argentina to determine mass loss and P and N concentrations of decaying leaf litter and roots of Poa ligularis (high-quality litter) and Stipa gynerioides (poor-quality litter). Leaf litter and roots of each species were incubated on sites dominated by P. ligularis and on sites dominated by S. gynerioides, to separate species from site effects. The experiment lasted up to 21 months. Mass loss of leaf litter and roots was higher (p<0.01) in P. ligularis than in S. gynerioides. Mass loss of leaf litters were higher (p<0.01) on P. ligularis sites, whereas mass loss of roots were similar (p>0.05) on both type of sites. Both species showed similar pattern of P and N dynamics in the leaf litter and roots, but net mineralization was higher (p<0.01) in P. ligularis than in S. gynerioides.